Effect of Pulsed Current Frequency and Anodisation Time on Surface Properties of Electropolished and Nonelectropolished Titanium Substrates - Marba, Victoria da Costa [UNESP]; Regone, Natal N. [UNESP]; Codaro, Eduardo N. [UNESP]; Acciari, Heloisa A. [UNESP] (Hindawi Ltd, 2018)
Surface characteristics of anodic films formed on electropolished and nonelectropolished titanium substrates have been evaluated using different sets of anodisation parameters at room temperature. Surfaces were analysed by light microscopy, Raman spectroscopy, scanning electron microscopy, and X-ray diffraction. The formation of TiO2 anatase phase was only detected on nonelectropolished substrates and there seems to be a larger amount of anatase as samples are anodised; consequently, the smallest crystals were obtained at the highest frequency of pulsed current. EIS results showed that there is no difference in the degree of compactness along the layer thickness.